Effects of parental empathy and emotion regulation on social competence and emotional/behavioral problems of school‐age children - Kun Meng; Yizhe Yuan; Yali Wang; Jianning Liang; Lijun Wang; Jianfei Shen; Yanyu Wang (Wiley, 2020)
ABSTRACT Importance Parents take the lead in parent-child interactions and their emotion regulation ability and empathy during parenting may be associated with children's emotional/behavioral problems. However, the specific mechanisms underlying these associations remain unclear. Objective The present study aimed to explore the effect of parental empathy and emotional regulation on social competence and emotional/behavioral problems in school‐age children. Methods A questionnaire‐based survey was conducted with 274 parents of 8-11‐year‐old children using Achenbach's Child Behavior Checklist, the Emotion Regulation Questionnaire, and the Questionnaire of Cognitive and Affective Empathy. Results Children with emotional/behavioral problems (n = 37) had relatively lower social competence than children in a matched control group (n = 37). Compared with the parents of children in the control group, parents of children with emotional/behavioral problems had significantly lower cognitive empathy scores, mainly manifested by low perspective‐taking and online simulation abilities. Mediation analysis showed that parental cognitive empathy had an indirect effect on children's emotional/behavioral problems through children's social competence. Interpretation Parental empathy may have a subtle influence on the social competence of school‐aged children, which further affects the severity of children's emotional/behavioral problems.